Art Therapy Melukis di Atas Kain Bagi Warga Binaan Lembaga Pemasyarakatan di Surabaya - Anindya Arum Cempaka; Maria Theresia Arie Lilyana (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
Various kinds of problems and pressures inmates (WBP) face during the punishment can trigger psychiatric issues. These psychiatric problems can manifest as actions that harm the environment or each other. Humans themselves are never separated from the dynamics of emotions in their lives. However, when life is at its lowest point, negative emotions spiral out of control and become a ticking time bomb. Negative emotions at their peak need to be channeled so as not to destroy the human being himself. The channeling of negative feelings does not have to be conducted concretely through words but through a cathartic process through works of art. Artworks can be a symbolic embodiment of life storylines, trauma, or anxiety. Art therapy activities aim to be catharsis or release of emotions in dealing with life's pressures so that participants can feel more prosperous while serving their sentences. Evaluation of activities through observation and interviews with participants, and the results are 13 participants expressed satisfaction with the activities that had been carried out.